Description of the thermodynamics and fluid-phase behaviour of aqueous solutions of linear, branched, and cyclic amines - Jackson,G; Perdomo,Hurtado FA; Khalit,SH; Adjiman,CS; Galindo,A (AIChE Journal, 2021)
The SAFT Mie groupcontribution equation of state is used to represent the fluidphase behaviour of aqueous solutions of a variety of linear, branched, and cyclic amines. New group interactions are developed in order to model the mixtures of interest, including the like and unlike interactions between alkyl primary, secondary, and tertiary amine groups (NH2, NH, N), cyclic secondary and tertiary amine groups (cNH, cN), and cyclohexylamine groups (cCHNH, cCHN) with water (H2O). The groupinteraction parameters are estimated from appropriate experimental thermodynamic data for pure amines and selected mixtures. By taking advantage of the groupcontribution nature of the method, one can describe the fluidphase behaviour of mixtures of molecules comprising those groups over broad ranges of temperature, pressure, and composition. A number of aqueous solutions of amines are studied including linear, branched aliphatic, and cyclic amines. Liquidliquid equilibria (LLE) bounded by lower critical solution temperatures (LCSTs) have been reported experimentally and are reproduced here with SAFT Mie approach. The main feature of the approach is the ability not only to represent accurately the experimental data employed in the parameter estimation, but also to predict the vapourliquid, liquidliquid, and vaporliquidliquid equilibria, and LCSTs with the same set of parameters. Pure compound and binary phase diagrams of diverse types of amines and their aqueous solutions are assessed in order to demonstrate the main features of the thermodynamic and fluidphase behaviour.